Deucalion et les os de la mère - Aline Magnien (In Situ)
Even though materials possess objective characteristics, they also contain a whole part of mythology in the meaning given to this term by Roland Barthes or Roger Caillois, for the stone. Coming back to this filiation, this article recalls a number of myths or reveries about stones and underlines how the choices made in terms of construction, sculpture or Land Art often rely on a technical history at least as much as a mythicized and dreamed history. Through a path mixing art, architecture and literature, going from China to the United States as well as Greece and Italy, this article weaves threads and links between periods and techniques that may seem quite far apart. This temporal and geographical vagrancy establishes thus filiations and similarities, highlighting the symbolic richness of the materials and the existence of these traditions of which we are not always aware. In the art and architecture field, what is said and thought is at least as important as what is created.